Differential Expression of a Novel Gene in Response to Coronatine, Methyl Jasmonate, and Wounding in the Coi1 Mutant of Arabidopsis - Benedetti, Celso E. (American Society of Plant Physiologists, 1998)
Coronatine is a phytotoxin produced by some plant-pathogenic bacteria. It has been shown that coronatine mimics the action of methyl jasmonate (MeJA) in plants. MeJA is a plant-signaling molecule involved in stress responses such as wounding and pathogen attack. In Arabidopsis thaliana, MeJA is essential for pollen grain development. The coi1 (for coronatine-insensitive) mutant of Arabidopsis, which is insensitive to coronatine and MeJA, produces sterile male flowers and shows an altered response to wounding. When the differential display technique was used, a message that was rapidly induced by coronatine in wild-type plants but not in coi1 was identified and the corresponding cDNA was cloned. The coronatine-induced gene ATHCOR1 (for A. thaliana coronatine-induced) is expressed in seedlings, mature leaves, flowers, and siliques but was not detected in roots. The expression of this gene was dramatically reduced in coi1 plants, indicating that COI1 affects its expression. ATHCOR1 was rapidly induced by MeJA and wounding in wild-type plants. The sequence of ATHCOR1 shows no strong homology to known proteins. However, the predicted polypeptide contains a conserved amino acid sequence present in several bacterial, animal, and plant hydrolases and includes a potential ATP/GTP-binding-site motif (P-loop).